Penerapan Model Promosi Berbasis Web Captive Portal Hotspot dengan Manajemen Terpusat - Yutanto, Hariadi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
The current technological developments so rapidly with speed and supported the ease of internet services. The Internet has also become one of the main needs of everyday human life activities. Internet advertising media innovation is one of the key media promotion in following the development of technology. Web-based portal advertising hotspot media for internet connection services is the most widely used today, as almost all agencies, offices, hotels, restaurants, schools / internet service providers (ISPs) use this technology. Hotspot network management techniques on mikrotik router captive portal can be used as a web-based promotion media and can be used as a centralized and dynamic media settings. Advertising media can be determined by location by combining 2 methods ie eoip and bridge for lan network while eoip, vpn and bridge on wan network. The results of this research has been working optimally and implemented in the network lan STIE Perbanas Surabaya while for wan network has been tested using the internet network in several locations civitas house.